Progress in English Language Teaching Through English Teacher Working Group (MGMP) - Teachers’ Self-Awareness, Perception, and Feedback - Zuhairoh, Zuhairoh (Prominent, 2024)
This paper explores the progress made in English language teaching through the English Teacher Working Group (MGMP) in Indonesia, with a specific focus on teachers’ self-awareness, perception, and feedback. The study examines the ways in which teachers engage in self-reflection, seek feedback, and refine their teaching practices to enhance their effectiveness as educators and create a conducive learning environment.  By analyzing the impact of the English Teacher Working Group program on teachers’ professional development and collaboration, the study highlights the importance of regular meetings, workshops, and collaborative projects in facilitating the exchange of ideas and best practices among teachers. Purposive sampling was used combined with a survey questionnaire and interviews to acquire the data. The findings demonstrated that self-development as an element of professional development is often viewed favorably by EFL teachers. The feedback on the English Teacher Working Group program (MGMP) showed that most teachers find the program vital for advancing their teaching skills. However, there were concerns regarding the duration of the program and the need for more time for relevant theories and feedback. Overall, the results suggest that EFL teachers have positive perceptions of self-development and the MGMP program, but there may be areas for improvement. Through this research, the concept of MGMP emphasizes the significance of self-awareness, perception, and feedback in enhancing teaching practices and fostering collaboration, contributing to the continuous improvement of English language education and the development of competent English language learners.